2009
DOI: 10.1016/j.tra.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Employment suburbanisation, reverse commuting and travel behaviour by residents of the central city in the Paris metropolitan area

Abstract: show that the number of reverse commuters has significantly increased because the municipality of Paris has lost many jobs but few working residents whilst employment has developed in the suburbs. Reverse commuters are mainly and increasingly high income professionals whose workplace is located close to the central city in employment sub-centres that are well served by public transport. Consequently reverse commuters have lower than average car use although differences exist and are related to their profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 21 publications
4
43
1
3
Order By: Relevance
“…The result demonstrated that urban sprawl can be reduced by up to 62 % through implementing certain spatial strategies [6]. The studies specifically concentrated on an urban strategy to minimize urban sprawl.Other researchers have paid attention to the relationship between employment suburbanization and the growth of reversed commuting in the weekday travel behavior of working residents in Paris [7]. The findings of the research confirmed that the choice of transport depends on the workplace, and the gentrification of the municipality of Paris linked to its capacity to attract high-qualified jobs and to its proximity to sub-centers.…”
mentioning
confidence: 59%
“…The result demonstrated that urban sprawl can be reduced by up to 62 % through implementing certain spatial strategies [6]. The studies specifically concentrated on an urban strategy to minimize urban sprawl.Other researchers have paid attention to the relationship between employment suburbanization and the growth of reversed commuting in the weekday travel behavior of working residents in Paris [7]. The findings of the research confirmed that the choice of transport depends on the workplace, and the gentrification of the municipality of Paris linked to its capacity to attract high-qualified jobs and to its proximity to sub-centers.…”
mentioning
confidence: 59%
“…Little is known about how long it takes workers and households to transition to new spatial arrangements after a workplace relocation, say, by moving house, changing to a job located elsewhere or changing schools for children. There is a risk that decentralisation can lead to higher proportion of suburb-to-suburb commutes which may entail increases in car use as more workers travel farther [9].…”
Section: Polycentric Structure Examplesmentioning
confidence: 99%
“…Studies in the developed world have demonstrated that residential density or location has positive effect on trip rate, trip length and mode of travel of households of individuals (Aguilera et al, 2009;Aditjandra et al, 2010 andRichwood andGlazebrook, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%